PENGARUH BUDAYA ORGANISASI TERHADAP IKLIM ORGANISASI DAN KEPUASAN KERJA (Kajian pada Karyawan Koperasi Grup Cipta Sejahtera) - Aryanto, Rakhmadi Widyo; Astuti, Endang Siti; Kumadji, Srikandi (FIA UB, 2019)
Background of the research is that paradigm emerged employee turn-over ratio in koperasi is low, even though compared with the other organizational. Set from that idea, this research entitled â€œOrganizational Culture Influence towards Organizational Climate and Job satisfaction (A Research on Cipta Sejahtera Koperasi Group Employee)â€Â aim on organizational culure influence towards organizational climate and job satisfaction, and organizational climate influence towards job satisfaction. This research locate on Cipta Sejahtera Koperasi, categorise in explanatory research with qualitative methods and descriptive approach. Data collection techniques use quistionare that is shared towards 60 (sixty) employee of Cipta Sejahtera Grup koperasi which vary on age, education, gender, work period. Result of the resarch inidcates that (1) organizational culture have significant influence in organizational climate, (2) organizational climate have not significant influence towards job satisfaction, (3) and organizational culture have significant influence towards job satisfaction.